Iplementasi Bahasa Indonesia dalam Pendidikan Jasmani pada Siswa MA Ishlahul Amanah untuk Meningkatkan Kualitas Pembelajaran - Hidayatulloh, Tsani Abdul Rohman; Lestari, Lista Ayu; karim, Arul Fathul; Al-Fawwaz, Muhammad Rakha; Listiyani, Dona; Rizkyanfi, Mochamad Whilky (LPPM Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
This study aims to find out the implementation of Indonesian in Physical Education for Ishlahul Amanah Students to Improve the Quality of Learning. The use of Indonesian as a medium and means of learning at MA Ishlahul Amanah School is expected to better understand the material, instructions, and make students active in communicating with teachers. This method is a quantitative method, this study collected data through questionnaires from several MA Ishlahul Amanah students with a total of 50 people, consisting of 24 people from class XII (47%), 21 people from class XI (41%) and 6 people from class X (12%). The instrument we did was in the form of a questionnaire with a question about communication and soldering in Indonesian. The results of the study show that the use of Indonesian in Physical Education contributes to class discussions and facilitates better communication between teachers and students. These results provide important information for the development of teaching at the level of Education at MA Ishlahul Amanah School, especially improving the quality of Physical Education